2019
DOI: 10.1093/gbe/evz018
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Genomics Reveals the Genetics and Evolution of the Honey Bee’s Social Immune System

Abstract: Social organisms combat pathogens through individual innate immune responses or through social immunity—behaviors among individuals that limit pathogen transmission within groups. Although we have a relatively detailed understanding of the genetics and evolution of the innate immune system of animals, we know little about social immunity. Addressing this knowledge gap is crucial for understanding how life-history traits influence immunity, and identifying if trade-offs exist between innate and social immunity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 98 publications
3
38
0
Order By: Relevance
“…Indeed, some loci appear to be linked to more than one social immunity trait ( Figure 5). For instance, some of the SNPs from the HYG investigations of Harpur et al (2019) fall within the locus found by Tsuruda et al (2012) when investigating VSH. However, more often, studies did not report the same regions to be involved, whether they were investigating the same trait or not.…”
Section: Identifying Social Immunity Pathwaysmentioning
confidence: 92%
See 2 more Smart Citations
“…Indeed, some loci appear to be linked to more than one social immunity trait ( Figure 5). For instance, some of the SNPs from the HYG investigations of Harpur et al (2019) fall within the locus found by Tsuruda et al (2012) when investigating VSH. However, more often, studies did not report the same regions to be involved, whether they were investigating the same trait or not.…”
Section: Identifying Social Immunity Pathwaysmentioning
confidence: 92%
“…Wider QTL bars indicate that the QTL was identified in more than one study. Genomic studies included Arechavaleta-Velasco et al 2012, Bourgeois et al 2016, Behrens et al 2012, Lattorff et al 2016, Conlon et al 2018, Conlon et al 2019, Tsuruda et al 2012, Spötter et al 2012, Harpur et al 2019, Oxley et al 2010, and Spötter et al 2016). The details of the genes, traits, and references are presented in Table S1 to S4.…”
Section: Figure 5 Comparison Of Genomic Regions Identified By the DImentioning
confidence: 99%
See 1 more Smart Citation
“…4). Dscam2 is implicated in axon guidance in Drosophila (Millard et al 2007) and in regulation of social immunity behavior in honeybees (reviewed by Cremer et al 2007;Harpur et al 2019). The EvoPrint scorecard ( fig.…”
Section: Conserved Sequence Elements In Bees and Antsmentioning
confidence: 99%
“…5). The Drosophila Gsc homeodomain transcription factor is required for proper axon wiring during embryonic CNS development and has recently been linked to social immunity behavior in honeybees (reviewed by Cremer et al 2007;Harpur et al 2019). The Drosophila Cas Zn-finger transcription factor has been shown to be essential for neuroblast temporal identity decisions during neural lineage development (Baumgardt et al 2014;reviewed by Brody and Odenwald 2007).…”
Section: Conserved Sequence Elements In Bees and Antsmentioning
confidence: 99%